2014
DOI: 10.2337/db13-1251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Epigenetic Histone Modifications in the Metabolic Memory of Type 1 Diabetes

Abstract: We assessed whether epigenetic histone posttranslational modifications are associated with the prolonged beneficial effects (metabolic memory) of intensive versus conventional therapy during the Diabetes Control and Complications Trial (DCCT) on the progression of microvascular outcomes in the long-term Epidemiology of Diabetes Interventions and Complications (EDIC) study. We performed chromatin immunoprecipitation linked to promoter tiling arrays to profile H3 lysine-9 acetylation (H3K9Ac), H3 lysine-4 trimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
145
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(157 citation statements)
references
References 51 publications
(51 reference statements)
3
145
0
6
Order By: Relevance
“…Notably, it is unknown if DNA-me persists over time in people with diabetes and is associated with metabolic memory. Here, we addressed this issue by using DNA collected at two different time points (EDIC Study baseline and EDIC Study years 16 and 17) from the same DCCT/EDIC Study cohort in which we previously evaluated histone PTMs (31). To our knowledge, this study is the first one in which two sets of DNAs collected at least 16-17 y apart from the same participants are used to show the persistency of DNA-me over time.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, it is unknown if DNA-me persists over time in people with diabetes and is associated with metabolic memory. Here, we addressed this issue by using DNA collected at two different time points (EDIC Study baseline and EDIC Study years 16 and 17) from the same DCCT/EDIC Study cohort in which we previously evaluated histone PTMs (31). To our knowledge, this study is the first one in which two sets of DNAs collected at least 16-17 y apart from the same participants are used to show the persistency of DNA-me over time.…”
mentioning
confidence: 99%
“…Several laboratories, including our laboratory, using cell and animal models have suggested roles for key histone PTMs in high glucose (HG)-mediated effects, diabetic complications, and metabolic memory (9,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Histone PTM profiling of vascular and inflammatory cells cultured with HG vs. normal glucose (NG) or WBCs from T1D patients vs. healthy volunteers or T1D patients with complications vs. those without depicted significant PTM differences and candidate differentially methylated or acetylated genes relevant to diabetes or its complications (23,(32)(33)(34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Chez ces patients, les complications du diabète causées par l'hyperglycémie transitoire persistent voire progressent, alors même que la glycémie est contrôlée par l'administration d'insuline [51]. L'analyse des modifications post-traductionnelles des histones dans des cellules sanguines de patients atteints de diabète de type 1 (DT1) a montré que l'acétylation de la lysine 9 de l'histone H3 (H3K9ac) est modifiée [52]. De façon similaire, in vitro dans des cellules endothéliales primaires exposées à une hyperglycémie, cette acétylation de l'histone H3 est diminuée sur un nombre significatif de régions promotrices de gènes impliqués dans la physiopathologie du DT1 [53].…”
Section: Discussionunclassified
“…In vascular smooth muscle cells derived from type 2 diabetic mice, irreversibly decreased levels of both H3K9me3 and methyltransferase Suv39H1 at the promoters of interleukin-6 and monocyte chemoattractant protein1 are observed, and SUV39H1 gene silencing irreversibly elevates the expression of inflammatory genes and decreases H3K9me3 at their promoters [57]. Monocytes from case subjects enrolled in landmark the Diabetes Control and Complications Trial and the follow up Epidemiology of Diabetes Interventions and Complications study have shown a significant association between H3K9 acetylation and hemoglobin A1C levels [58].…”
Section: Epigenetic Modification and Diabetesmentioning
confidence: 99%